2019
DOI: 10.3390/jcm8020162
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Depletion is Effective in Ameliorating Anxiety-Like Behavior and Reducing the Pro-Inflammatory Environment in the Hippocampus in Murine Experimental Autoimmune Encephalomyelitis

Abstract: The neuropsychiatric symptoms of multiple sclerosis (MS), such as anxiety and depression, can result from disease activity itself as well as psychological reaction to an unfavorable diagnosis. Accordingly, the literature reports evidence of increased anxiety-like behavior in experimental autoimmune encephalomyelitis (EAE), an accepted MS model. Due to the recently described critical role of platelets in inflammation and autoimmune disease, we examined the relationship between platelets, inflammation, and anxie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 53 publications
1
35
0
Order By: Relevance
“…Immunofluorescence was performed as described previously with some modification [32,33]. Slides with brain sections were washed twice with 1% PBS for 10 min, then proteinase-k was added, followed by incubation for 5 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Immunofluorescence was performed as described previously with some modification [32,33]. Slides with brain sections were washed twice with 1% PBS for 10 min, then proteinase-k was added, followed by incubation for 5 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Addressing neuropsychiatric symptoms of MS, such as anxiety and depression, it has recently been shown that GPIb antibody-mediated platelet depletion prevented the EAE-induced increase in anxiety-like behavior which was associated with reduction of the pro-inflammatory environment to control levels in the hippocampus of mice ( 166 ).…”
Section: Contribution Of Platelets To Neurovascular Inflammation In Nmentioning
confidence: 99%
“…Recent work investigating the brains of EAE-induced mice demonstrated that platelets were also present in the parenchyma of the hippocampus, including in the fimbria and in close proximity to neuronal cell bodies in the dentate gyrus and CA1 region (14). This phenotype was associated with the formation of a neuroinflammatory environment, supposedly due to plateletneuron associations (14).…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…This phenotype was associated with the formation of a neuroinflammatory environment, supposedly due to plateletneuron associations (14). However, this occurred in the absence of inflammatory cell infiltration, further highlighting the role of platelets in the initiation of EAE (14). In the same study, the pro-inflammatory environment in the hippocampus of EAEinduced mice, as well as their increased anxiety-like behavior, were improved following platelet depletion with polyclonal antiplatelet glycoprotein Ib α chain antibodies, suggesting that platelets could serve as a potential target for the amelioration of the symptoms of MS (14).…”
Section: Multiple Sclerosismentioning
confidence: 99%
See 1 more Smart Citation